Unity 2022 mobile game development : build and publish engaging games for Android and iOS - Doran, John P., 1988 or 1989- (Packt Publishing Ltd., 2023)
Unity is a well-established player in the mobile game development sphere, and its new release, Unity 2022, is packed with new, exciting features. In Unity 2022 Mobile Game Development, the third edition in this popular series, you'll get to grips with the Unity game engine by building a mobile game and publishing it on the most popular mobile app stores as well as exploring the all-new features. This book provides a comprehensive and practical approach to mobile game development, helping you build an endless runner game. Starting with setting up a simple Unity project for mobile development, you'll delve into various essential aspects needed to successfully create and publish your game. You'll acquire a range of skills, such as incorporating touch gestures, monetizing your game with Unity Ads and in-app purchases, designing an intuitive UI, and seamlessly integrating social media functionalities. Additionally, you'll gain valuable insights into player preferences and behavior using Unity's analytics tools. You'll also explore features of augmented reality in Unity 2022, enhancing your game's appeal. By the end of this book, you'll be well-equipped to reap the power of Unity 2022 to build, optimize, and publish robust cross-platform mobile games with C#, as well as widening your skill set and enhancing your credentials as a game developer.